MENINGKATKAN KEMAMPUAN MENEKAN TOMBOL KEYBOARD MELALUI LATIHAN TAKTAIL DAN KINESTETIK BAGI ANAK CEREBRAL PALSY KELAS VII DI SMP N 23 PADANG (Single Subject Research) - Darmiati - Darmiati (Jurnal Penelitian Pendidikan Khusus, 2013)
This research of  background overshadow by problem of a child cerebral palsy of class VII with find difficulties in button keyboard. Of result identify and asesmen, child find difficulties in button keyboard better and correctness. Hence from that researcher cope to assist to increase ability button keyboard by using practice of taktil and of kinestetik. This research aim to increase ability button keyboard through usage of practice of tactil kinestetik to cerebral palsy of child. This research using approach of experiment in the form of Single Subject Research (SSR) designed by A-B and technique analyse its data use visual analysis of graph of analysis in a condition and analyse between condition. Assessment in this research that is by giving media at child to practice the way of button keyboard. For its goals of him that is frequency if child can button keyboard better and correctness given by value 1, and if child unable to button keyboard is truly given by value 0. Result of this research indicate that pursuant to result of good data analysis or analysis in a condition and also analyse between condition show estimation tendency of direction, tendency of stability, data footstep and rate of change which mounting positively and also overlop at data analysis smaller. Hence thereby can be expressed by research hypothesis (Ha) accepted. From result of entirety show the existence of change of ability button keyboard at child of J toward better. Matter this means can be concluded that kinestetik tactil ltihan can be used in improving ability button keyboard to cerebral palsy of child. Hence researcher suggest to teacher to use practice of tactil kinestetic in improving ability button keyboard.